Bosnia and Herzegovina : Poverty Reduction Strategy Paper-Mid-Term Development Strategy. (IMF Staff Country Reports; Country Report, 2004)
Poverty risk is most marked for children, displaced persons and returnees, unemployed, and people with low education. Basic goals of the macroeconomic framework of the mid-term development strategy of Bosnia and Herzegovina are to reduce the overall public expenditures, lower the public debt, and to bring the current account deficit to a sustainable level through fiscal consolidation. The strategy is to attract more foreign investment, create conditions for a more efficient privatization process, and to ensure new cycles of donor assistance.